“When Crisis Becomes Growth”: Meaning-Making, Resilience, and Growth among Adolescents with Out-of-Wedlock Pregnancy - Sahertian, Eunike Adelya Elaina; Adiyanti, Maria Goretti; Wahyuningrum, Enjang (Kuras Institute, 2025)
This study investigates the meaning-making process of negative experiences among adolescents who experienced out-of-wedlock pregnancy. Using a qualitative phenomenological approach, data were collected from five participants (17 to 19 years old when they got first pregnancy) through in-depth interviews and observations to explore their emotional and cognitive responses. The findings showed that the meaning-making process is gradual and shaped by both internal and external factors. Initially, the pregnancy was perceived as traumatic, marked by shame, fear, and social rejection. Over time, however, support from family and friends played a key role in helping the adolescents reinterpret their experiences. Family support, in particular, provided a safe, nonjudgmental space that enabled emotional recovery and personal reflection. This shift allowed the participants to develop a sense of responsibility, continue their education, seek economic independence, and pursue healthier relationships. These efforts reflect a transition from crisis to growth, guided by a “will to meaning” and the creation of purpose through action. In conclusion, out-of-wedlock pregnancy, while initially distressing, became a catalyst for personal development and a deeper understanding of life’s meaning.